ANALISIS KADAR HDL PADA PEROKOK AKTIF DEWASA USIA 31-35 TAHUN DI RT. 03. RW.01 KELURAHAN KEMAYORAN BANGKALAN - Haris, M. shofwan (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2021)
Smoking is one of the health problems that is difficult to solve even has become a national and international problem. One of the negative effects of smoking is a decrease in HDL levels in the body. The purpose of this study was to determine the description of HDL levels in active adult smokers aged 31-35 years in RT.04 / RW.01 Mlajah Bangkalan Village. This research is a descriptive study, with a research design using cross sectional design. The variable of this study is the level of HDL in active smokers with a population of 15 respondents selected as samples using total sampling. The data collection method uses a photometer, the data obtained are then presented in a frequency distribution table. The results of research on HDL levels of active smokers mostly low HDL levels less than 60 mg / dl with 11 respondents (73.33%) .This happens because the nicotine contained in cigarette smoke will stimulate the hormone adrenaline which will consequently interfere with fat metabolism which causes HDL levels in the body decrease. From the results of this study it is expected that a smoker should reduce smoking habits and better carry out regular health checks.